Oxyspiruriasis in zoo birds - Vellayan, S.; Jeffery, J.; Oothuman, P.; Zahedi, M.; Krishnasamy, M.; Paramaswaran, S.; Rohela, M.; Abdul-Aziz, N.M. (2012)
Oxyspiruriasis caused by the bird eyeworm, Oxyspirura mansoni, a thelaziid nematode, in three species of pheasants, 3 Chrysolophus pictus (golden pheasant), 7 Lophura nycthemera (silver pheasant) and 9 Phasianus colchicus (common pheasant) in Zoo Negara Malaysia are reported. Birds with the disease were treated with a solution of 0.5 iodine or 0.5 lysol. Antistress powder for 4 days in water and non-strep vitamin powder in water was also provided. Control measures included removal of the cockroach intermediate host, Pycnoscelus surinamensis (Surinam cockroach) from the vicinity of the birds. The golden pheasant is a new host for O. mansoni in peninsular Malaysia.